Impact of coronavirus disease pandemic on antimicrobials consumption and antimicrobial resistance during the first and second wave in a tertiary care hospital, in India - Bhardwaj, Ankit; Agarwal, Rohit; Mangesh, Mala; Bhardwaj, Avyukt (International Journal of Basic & Clinical Pharmacology, 2023)
Background: This study measured the impact of the first and second wave of COVID-19 pandemic (in the year 2020-21) on the antibiotics uses and their effect on gram nehative bacterial species Klebsiella, Enterobacter, Pseudomonas and Acinetobacter. Methods: The number of patient admission month-wise, antibiotic consumption, blood cultures collected, number of positive BCs, and antibiotic resistance were analysed retrospectively for the years 2020, 2021, and 2019 for comparison, in tertiary care hospital (ca. 840 beds). Results: Half of patients admitted in years 2020 and 2021 in our hospital had COVID-19. A significant increase in total antibiotic consumption during the years 2020 (75.53 DDD per 100 admissions) and 2021 (91.71 DDD per 100 admissions) occurred in comparison to the year 2019 (52.5 DDD per 100 admissions). The rate ratio of BCs per 100 admissions increased by 74% in the year 2020, and 118% in the year 2021 in comparison with the rate ratio to the year 2019. The BSI rate per 100 admissions increased overall by 24% in March 2020 and 115% in April 2020, the rate ratio of BSIs per 100 admissions raised 58.4% for Klebsiella and 239.3% for E. coli, but remain the same for Acinetobacter and Aeruginosa. A sharp increase in the rate of BSIs caused by microorganisms resistant to cephalosporins was also observed in the years 2020 and 2021. Conclusions: present study highlights the impact of the first and second waves of the COVID-19 pandemic on antibiotic consumption and the increasing prevalence hospital-acquired infections and antimicrobial resistance.